2002
DOI: 10.2174/1568026023394245
|View full text |Cite
|
Sign up to set email alerts
|

RNA and RNA-Protein Complexes as Targets for Therapeutic Intervention

Abstract: Today, the majority of pharmaceuticals developed to treat cancers and viral/bacterial infections target cellular, bacterial or viral proteins known to be associated with a given pathology. Although proteins are the focus of most current drug discovery efforts, exciting new research has recently begun which aims to exploit ribonucleic acid (RNA) and RNP particles as novel targets for pharmaceutical development. These RNA-targeted research efforts have been fueled by an increased appreciation for the central rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Dervan and colleagues have been quite successful in designing molecules that target specific sequences in DNA (31), but that technology does not exist for targeting specific RNA structures and sequences. Efforts are currently underway to understand the rules of small molecule-RNA interactions (32,33). To determine whether CUG repeats could be targeted by small molecules we screened a small library of known nucleic acid binding molecules and found that pentamidine and neomycin B bound CUG repeats and could displace MBNL1 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Dervan and colleagues have been quite successful in designing molecules that target specific sequences in DNA (31), but that technology does not exist for targeting specific RNA structures and sequences. Efforts are currently underway to understand the rules of small molecule-RNA interactions (32,33). To determine whether CUG repeats could be targeted by small molecules we screened a small library of known nucleic acid binding molecules and found that pentamidine and neomycin B bound CUG repeats and could displace MBNL1 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Structural RNAs and RNPs are attractive targets for therapeutic development (DeJong et al 2002;Goodchild 2004). For example, many of the best antibacterial antibiotics target the ribosome by binding to ribosomal RNA at sites that differ slightly between prokaryotes and eukaryotes (Recht et al 1999;Lynch et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Beside ribozymes, RNA antisense, and RNA interference techniques, [15][16][17][18] RNA targeting using low-molecular weight compounds represents a young but dynamic field. 19,20 Today, only a few systems are used as models for the study of the molecular recognition of drugs by RNA molecules, 21,22 with the design of rational drugs as the ultimate goal. 23 Particularly, aminoglycoside antibiotics form the most studied family of RNA binding drugs.…”
Section: Introductionmentioning
confidence: 99%